Anti-diabetic (AD) and hardness profile of 12-(4-Chlorophenyl)-9, 9- Dimethyl-9, 10-Dihydro-8H-benzo[a]xanthen-11(12H)-one –(CPDDHBXH) – Comparative analysis of macro and nano crystals. (2020) - Senthilkumar, R.; Senthilkannan, .K.; Udhayakumar, S.; Narayanan, S.T. Aadithya
Abstract: As the CPDDHBXH full scale and nano crystals are having gargantuan effect on opto-electronic applications, stage coordinating, recurrence coordinating and power transmission and different sorts of utilities in bio and with drug store fields, it is the extent of the physicists and electronic friends to create and consider the exceptional capacities like nano tribological factors and different utilities. Full scale crystals have littlest sum pertinent relationships by estimation disparity to nano outline of CPDDHBXH equipped by mill recital. The nano form of CPDDHBXH crystals are of 22 nm respectively, the XRD data reveals the macro crystals are having the formula C25 H21 ClO2 are of a = 10.293 Å, b = 11.621 Å, c = 16.447 Å, β = 90.04°, monoclinic with space group P21 /n, the macro level NLO is nearly 2 times higher than that of typical KDP. Here, both the macro and nano crystals are undergone with AD work and hardness profile studies and reported, CPDDHBXH are best for electronic filters and for frequency converters stand on their macro stage NLO-SHG efficiency.